Pengabdian Kepada Masyarakat Melalui Ekonomi Kreatif Bedak Dingin B-Cool Kelurahan Bulang Lintang Kota Batam - Reny Haryani; Suci Fitriani Sammulia; Arie Vonikartika; Yunisa Friscia Yusri (Jurnal Pengabdian Ilmu Kesehatan, 2022)
Cold powder is a mixture of starch with fragrant ingredients, sometimes added with moisturizing, ultraviolet light blocking and antiseptic ingredients in the form of small dry granules, having a color and aroma according to its composition. The main raw material in the process of making cold powder is rice flour. The function of rice flour is to soften the skin. The stages of making cold powder are mixing the ingredients, rolling, and drying. The aim of this community service activity is to introduce the benefits of natural ingredients such as rice flour and turmeric in overcoming facial skin beauty problems and empowering the community in producing simple turmeric cold powder products in order to implement the Creative Economy program in the RT 02 community of Bulang Lintang village. The method used is through demonstration. The results of the activity show that the community is able to make their own B-Cool cold powder in order to implement the Creative Economy program.